Law Enforcement of Black Market Handphone Sales in The Internasional Scope - Fayza Galih Nur Rohmah; Rina Arum Prastyanti (Greenation Research & Yayasan Global Resarch National, 2023)
Almost everyone now uses mobile phones to make it easier to get information remotely. The development of cellphones is also much more sophisticated in today's contemporary era. With these developments, consumer interest in communication tools is increasing, providing business people with business opportunities. even when business actors obtain these tools illegally or on the black market. The aim of this research is to identify and discuss law enforcement applied to blackmarket cellphone sales as well as the main factors that cause more cases of blackmarket cellphone sales.